Progress and prospects of organoids in the pathogenesis of lung cancer and screening of antitumor drugs - Li, Yiqiong; Shang, Yuanjie; Zhang, Na; Li, Jiarui; Yang, Zijiang (Frontiers in Oncology, 2026)
Lung cancer, a major global public health issue for decades, is characterized by high incidence and mortality rates. Over the past twenty years, numerous novel therapies have emerged. However, due to the substantial genetic and phenotypic heterogeneity among patients, current treatment modalities still yield low cure rates for advanced lung cancer, creating an urgent need to develop precision medicine aided by personalized tumor models. The rise and advancement of three-dimensional organoid culture technology have brought new hope to this endeavor. Patient-derived organoids can closely mimic the in vivo biological characteristics of lung cancer, enabling the exploration of its pathogenesis and the effective screening of anticancer drugs, thereby facilitating progress in precision medicine for lung cancer. This review provides a systematic analysis by constructing a framework that spans foundational techniques, mechanistic investigations, preclinical applications, and integration with emerging technologies. It specifically highlights the role of organoids in simulating the dynamic evolution of lung cancer, deciphering tumor heterogeneity, and serving as a versatile platform for convergence with cutting-edge tools such as organs-on-chips, 3D bioprinting, and CRISPR-Cas9. Furthermore, the review discusses the key challenges and limitations facing lung cancer organoid models and outlines their future prospects for broader application.